The Concept of Word in The Quran - Karataş, Yahya (Fırat University, 2022)
The Qur'an is a divine revelation with an addressing style based on the communication language used by the society to which it was revealed. Therefore, the first addressees of the Qur'an mostly understood the message of the revelation and what was meant to be conveyed. These first addressees, known for their interest in literature, noticed this ijaz aspect of the Qur'an from the beginning of the revelation. The Qur'an has many qualities. One of its most important features is that it uses a part of the concept to have different meanings depending on its place. One of them is the concept of "word". This concept, which is mentioned forty-six times in the Qur'an, sometimes has the same meaning, and sometimes it has different meanings with some suffixes. Some of the compositions in which this word is used in the Qur'an are: kalimatu'l-fasl, el-kelimu't-tayyib, kalimatu'l-kufr, kalimatu'l-azap, kalitu'l-fasl, kalimatu't-taqwa... This concept has gained different meanings in different parts of the Qur'an, both according to the context in which it is used and the meaning it expresses. As it can be understood from here, the Qur'an has interfered with the words and concepts used by the society to which it was sent from time to time and has been able to ascribe different meanings. In the final analysis, the concepts have taken on a different identity with the new meanings that the Qur'an has brought to them, and they have now been used based on that meaning.

Kur’an, indirildiği toplumun kullandığı iletişim dilini esas alan bir hitap tarzına sahip ilâhî vahiydir. Bu yüzden ilk muhataplar gelen vahyin dilini çoğunlukla anlamışlardır. Ancak Kur’an’ın önemli özelliklerinden birisi de bir kısım kavramı farklı manalarla kullanmasıdır. Bunlardan birisi de “kelime” kavramıdır. Kur’an’da toplam kırk altı kez geçen bu kavram bazen aynı anlamda, bazen de aldığı bazı eklerle beraber farklı anlamlara gelebilmiştir. Kelime, kelimetullah, kelim bunlardan bir kaçıdır. Bu kavram, hem geçtiği bağlama göre hem de ifade ettiği manaya göre Kur’an’ın farklı yerlerinde farklı anlamlar kazanmıştır. Buradan da anlaşılacağı üzere Kur’an zaman zaman gönderildiği toplumun kullandığı kelime ve kavramlara müdahale etmiş ve farklı anlamlar yükleyebilmiştir.
Kur’an’da Kelime Kavramı
Keywords: Religious Studies; Din Araştırmaları